2018
DOI: 10.1007/s10545-018-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Velmanase alfa in the treatment of patients with alpha‐mannosidosis: results from the core and extension phase analysis of a phase III multicentre, double‐blind, randomised, placebo‐controlled trial

Abstract: These findings support the utility of VA for the treatment of AM, with more evident benefit over time and when treatment is started in the paediatric age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 17 publications
1
38
0
4
Order By: Relevance
“…Early diagnosis is important to minimize uncertainty for affected families and might help to make informed decision in family planning. Pediatric patients achieved better treatment results than adults with alpha‐mannosidosis in clinical trials of specific therapies suggesting that early diagnosis and early treatment may be of importance for positive effects. Making the diagnosis includes clinical pattern recognition (Figure ) , the measurement of elevated oligosaccharides in serum or urine, demonstration of alpha‐mannosidase enzyme deficiency, and mutational analysis of the MAN2B1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis is important to minimize uncertainty for affected families and might help to make informed decision in family planning. Pediatric patients achieved better treatment results than adults with alpha‐mannosidosis in clinical trials of specific therapies suggesting that early diagnosis and early treatment may be of importance for positive effects. Making the diagnosis includes clinical pattern recognition (Figure ) , the measurement of elevated oligosaccharides in serum or urine, demonstration of alpha‐mannosidase enzyme deficiency, and mutational analysis of the MAN2B1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Velmanase alfa was tested in humans in a phase I/II (10 patients) and a phase III study (25 patients between five and 35 years of age, duration of 52 weeks, dose/frequency/administration: 1 mg/kg weekly, IV). In the phase III study, a statistically significant reduction on a biomarker endpoint (serum oligosaccharides) was achieved (adjusted mean difference for velmanase alfa vs placebo −70.5% [95% CI −78.4 to −59.7; P < .001]), however, the clinical co‐primary endpoint 3‐minute stair climb test showed no difference to placebo . The authors suggested that early intervention may be of importance in the future .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hematopoietic stem cell transplant (HCT) has been shown to positively impact developmental outcome in alpha‐mannosidosis in several patients . More recently, enzyme replacement therapy has been approved for treating the non‐neuropathic features of the disease in the EU with orphan drug designation …”
Section: Introductionmentioning
confidence: 99%
“…5,6 More recently, enzyme replacement therapy has been approved for treating the nonneuropathic features of the disease in the EU with orphan drug designation. 2,7,8 Reports on intellectual function in alpha-mannosidosis are scarce. One set of measures of effectiveness of therapies is impact on IQ.…”
Section: Introductionmentioning
confidence: 99%